Islam - Abd al-Rahman Tayyara (International Institute of Islamic Thought, 2006)
In his book Islam: Practices · Holy Texts · Sacred Persons · Sacred Places, Matthew Gordon discusses the divinely revealed nature of Islam through texts, persons, times, and places. His book is a welcome addition to a new wave of introductory books written by western scholars who seek to present Islam objectively to western readers. The book’s main argument is that, like other monotheistic religions, Islam is based on a set of divine beliefs that revolve exclusively around perceiving God through His many signs. These manifestations of God are evident in the religious texts, persons, times, and places that have figured in Islam since its inception. At the same time, Gordon argues that the Islamic tradition “is far from monolithic and is the product of many centuries of scholarship and internal debate” (p. 67). The target audience of this book is general readers and beginners in the field who are looking for a handy textbook on the subject. This slim book is divided into nine chapters, each of which ends with a commentary on a selected text that elucidates the theme discussed, and includes a glossary, bibliography, and an index. Its style is clear and simple. As the most important source of Islam’s genealogy, the Qur’an plays a major role in this study. In the first chapter, Gordon offers a brief historical review of Islam’s religious and political development. By presenting different Islamic dynasties that ruled various parts of the world, the author reveals how Islam reached non-Arab peoples, which explains the fact that the majority of today’s Muslims live in Southeast Asia rather than the Middle East. In the second chapter, the author discusses the axis around which the set of Islamic beliefs and practices revolves. Gordon rightly argues that the divinely revealed nature of Islam stems absolutely from God’s pivotal place in Islam. Specifically, he claims that “[t]he relationship between Muslims and God is informed by three principles that derive directly from the Quran” (p. 24): the “divine unity of God (tawhid),” “prophecy (nubuwwa),” and the “last days (maad).” At the same time, Gordon highlights the differences between Sunni and Shi`i Islam and also refers to two other principles that are exclusive to the Shi`i tradition: imamate and divine justice. Gordon’s discussion of Sufism takes up a considerable part of this chapter because, for ...